2017
DOI: 10.1177/1757177416680442
|View full text |Cite
|
Sign up to set email alerts
|

Public perceptions of the use of gloves by healthcare workers and comparison with perceptions of student nurses

Abstract: Introduction: There is evidence that non-sterile clinical gloves (NSCG) are over-used by healthcare workers (HCWs) and are associated with cross-contamination. This study aimed to determine attitudes of student nurses and members of the public to the use of NSCG.Methods: Third-year student nurses completed a questionnaire indicating tasks for which they would wear NSCG and influences on their decision. Correlations between tasks were identified using exploratory factor analysis. An online survey of the publi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
13
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 16 publications
1
13
0
1
Order By: Relevance
“…This study demonstrated that in acute healthcare settings NSCG are commonly used for episodes of care where their use is not indicated. [3,6,8,16] They are donned too early, removed too late and not changed at critical points in the delivery of patient care. Consequently, NSCG-use is associated with a significant potential for cross-contamination and transmission of HAI.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This study demonstrated that in acute healthcare settings NSCG are commonly used for episodes of care where their use is not indicated. [3,6,8,16] They are donned too early, removed too late and not changed at critical points in the delivery of patient care. Consequently, NSCG-use is associated with a significant potential for cross-contamination and transmission of HAI.…”
Section: Discussionmentioning
confidence: 99%
“…[6,7] There is also some evidence that patients are concerned about the use of NSCG by HCW. [8] Human factors and ergonomics (HFE) is defined as "the scientific discipline concerned with the understanding of interactions among humans and other elements of a system, and the profession that applies theory, principles, data and methods to design in order to optimize human well-being and overall system performance". [9] The application of HFE in healthcare is an emerging science and while recent work has focused on medication safety, the design of health information technologies, and assessment of patient safety culture, the value of HFE in healthcare has yet to be fully realised.…”
Section: Introductionmentioning
confidence: 99%
“…Wilson et al (2017b) investigated the attitudes of UK student nurses to the use of NSG and found that the most frequently cited reason for the decision to wear gloves was their own judgement. Decisions were not always based on an accurate assessment of the risk of exposure to body fluids, gloves being used for low-risk tasks such as washing patients and helping them to dress.…”
Section: Introductionmentioning
confidence: 99%
“…Although public health authorities, such as the Centers for Disease Control and Prevention in the United States, do not currently recommend universal gloving, nurses report wearing gloves with every patient contact for their own protection (Baloh et al, 2019), a practice that creates a physical and, potentially, emotional barrier between nurses and their patients. Importantly, patients have reported discomfort with what they perceive as the 'overuse' of gloves for activities such as feeding, dressing, and assisted ambulation (Wilson, Bak, Whitfield, Dunnett, & Loveday, 2017).…”
mentioning
confidence: 99%